Pathological changes in the mammary gland of rabbits following intra-mammary inoculation of Mycoplasma agalactiae (Journal of Laboratory Animal Science, 2024)
Contagious agalactia is a disease predominantly of milking sheep and goats caused mainly by Mycoplasma agalactiae, clinically manifested as mastitis, arthritis, keratoconjunctivitis and pneumonia. Pathological changes in the mammary  gland of rabbits following intra-mammary inoculation of M. agalactiae were studied. Clinical mastitis developed within  24 hpi. It was initially acute but became chronic by the end of the experiment at 9 dpi. The disease was characterized by  atrophy of the infected mammary glands, resulting in marked agalactia. Histopathology revealed that the mastitis was acute  and purulent initially, followed by infiltration of mononuclear cells with fibroplasia in the interacinar tissue, and later by  massive fibrosis by 9 dpi.
Keywords: Contagious agalactia; Mycoplasma agalactiae; mastitis; rabbit; mammary gland